Internalization of Civic Disposition Values Through CIVIC EDUCATION Learning at SMA Negeri 30 Bone - Rismayanti, Rismayanti; Rasyid, Andi Tabrani; Ahmad, Ahmad; Rusdi, Muhammad (JUPE : Jurnal Pendidikan Mandala, 2023)
This research aims to, (1) determine the process of internalizing civic disposition values through PPKn learning at SMA Negeri 30 Bone, (2) determine the inhibiting factors in internalizing civic disposition values through PPKn learning at SMA Negeri 30 Bone. The type of research used is a qualitative descriptive research method. The data processed is the result of interviews with PPKn teachers and students at SMA Negeri 30 Bone. The data collection methods used in this research are observation, interviews and documentation, where the author directly sees the situation in the field. The results of the research show that: (1) The process of internalizing civic disposition values through PPKn learning at SMA Negeri 30 Bone is carried out through teaching and learning processes in class which are carried out directly or indirectly by PPKn teachers which are developed through teaching modules or RPPs which are used in accordance with applicable curriculum. To internalize the values of civic disposition through PPKn learning is also carried out using various methods, namely the habituation method, conversation method, exemplary method and reward and punishment method. (2) The inhibiting factors in internalizing civic disposition values through PPKn learning at State High School 30 Bone are the lack of enthusiasm of students in participating in the learning process, the influence of the family environment which has not been maximized in instilling civic disposition values, the influence of the environment around students such as student interactions. which is difficult to control and the influence of peers, and the negative impact of technological developments, such as the use of social media and digital entertainment or online content.